Behavioral Rehearsal Psychoeducation Reduces Social Anxiety Among Santri: Pendidikan Psikologis dengan Latihan Perilaku Mengurangi Kecemasan Sosial di Kalangan Santri - Nur Salsabiilaa Rahayu; Zaki Nur Fahmawati (Academia Open, 2025)
General Background: Social anxiety is a psychological condition frequently emerging during adolescence, particularly in intensive communal environments such as Islamic boarding schools where social interaction is highly demanded. Specific Background: Santri in Tahfidz Islamic Boarding Schools experience structured communal living that requires active participation, yet preliminary data indicated moderate to high levels of social anxiety among students. Knowledge Gap: Previous studies primarily examined Behavioral Rehearsal as a curative counseling technique in formal schools, with limited investigation of its application as structured psychoeducation within pesantren settings. Aims: This study aimed to examine the role of Behavioral Rehearsal psychoeducation in decreasing social anxiety among santri at a Tahfidz Islamic Boarding School in Sidoarjo. Results: Using a quasi-experimental one-group pretest-posttest design with 30 participants, analysis revealed a significant decrease in social anxiety scores (t = 6.262, p < .001) with a large effect size (Cohen’s d = 1.143), supported by Wilcoxon test results (p < .001). Novelty: The study introduces Behavioral Rehearsal as a structured psychoeducational program tailored to the collective pesantren context. Implications: Findings support integrating Behavioral Rehearsal psychoeducation into pesantren counseling programs to support adolescent psychological adjustment and social functioning. Keywords: Behavioral Rehearsal, Psychoeducation, Social Anxiety, Islamic Boarding School, Adolescent Psychology Key Findings Highlights: Significant decrease in anxiety scores after structured intervention sessions Large statistical magnitude indicating strong practical change Adapted role-play training suitable for communal religious education settings